2019
DOI: 10.1007/164_2019_284
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Information and Quality Standards for Conducting, Reporting, and Organizing In Vitro Research

Abstract: Insufficient description of experimental practices can contribute to difficulties in reproducing research findings. In response to this, "minimum information" guidelines have been developed for different disciplines. These standards help ensure that the complete experiment is described, including both experimental protocols and data processing methods, allowing a critical evaluation of the whole process and the potential recreation of the work. Selected examples of minimum information checklists with relevance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Scores of guidelines exist, many of which being compiled on the Enhancing the QUAlity and Transparency Of health Research (EQUATOR, https ://www.equat or-netwo rk.org/) network. The leading guidelines used in preclinical research is the Animal Research: Reporting of In Vivo Experiments (ARRIVE), which has been recently updated (ARRIVE 2.0 version) 5,6 but other official guidelines exist such as the one published by the American Physiological Society 7 , the Checklist for Reporting In-vitro Studies (CRIS) guidelines 8 and the checklist by Emmerich and Harris for in vitro research 9 . However, series of scoping reviews have documented that unclear and non-transparent reporting of statistical methods remain in the life preclinical literature 2,[10][11][12][13] , prompting the conclusion that these guidelines have had limited impact thus far [14][15][16] .…”
mentioning
confidence: 99%
“…Scores of guidelines exist, many of which being compiled on the Enhancing the QUAlity and Transparency Of health Research (EQUATOR, https ://www.equat or-netwo rk.org/) network. The leading guidelines used in preclinical research is the Animal Research: Reporting of In Vivo Experiments (ARRIVE), which has been recently updated (ARRIVE 2.0 version) 5,6 but other official guidelines exist such as the one published by the American Physiological Society 7 , the Checklist for Reporting In-vitro Studies (CRIS) guidelines 8 and the checklist by Emmerich and Harris for in vitro research 9 . However, series of scoping reviews have documented that unclear and non-transparent reporting of statistical methods remain in the life preclinical literature 2,[10][11][12][13] , prompting the conclusion that these guidelines have had limited impact thus far [14][15][16] .…”
mentioning
confidence: 99%
“…When asked about the cause, a proportion pointed towards poorly-characterized tools leading to ambiguous findings, which results in an unstable knowledge foundation that is then built upon. Since this survey, different guidelines for in vitro and in vivo research have been suggested, issued and published ( 125 , 126 ). Characterization of antibodies as well as validation of tools to quantify proteins is vital for every field, but particularly for the FH protein family considering the high risk of cross-reactivity due to their homology.…”
Section: Major Challengesmentioning
confidence: 99%
“…Another aspect is reporting, which was insufficient for many studies. Thus, papers should be checked prior to publication whether they adhere to well accepted reporting guidelines such as STROBE (STrengthening the Reporting of OBservational studies in Epidemiology) (von Elm et al 2007) or CONSORT (Consolidated Standards of Reporting Trials) (Schulz et al 2010), ARRIVE (Animal Research: Reporting of In Vivo Experiments) (Kilkenny et al, 2010;Percie Du Sert et al, 2020), and MIBBI (Minimum Information for Biological and Biomedical Investigations (Taylor et al 2008;Emmerich & Harris, 2020).…”
Section: Discussionmentioning
confidence: 99%